Efeito do óleo essencial de canela e cinamaldeído em biofilme de Salmonella Saintpaul em aço inoxidável - Piovezan, Michelle (2013)
Biofilm formation on surfaces has important consequences for health and food industry, since they can be a source of food contamination leading to food spoilage and foodborne diseases. This study evaluated the effect of cinnamon essential oil (EO) and cinnamaldehyde against Salmonella enterica serotype Saintpaul biofilms on stainless steel surface. The effects of cinnamon EO and cinnamaldehyde on biofilms was evaluated in 96-well plates using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) staining. Colony forming units (CFU) counting assays and scanning electron microscopy (SEM) were used to evaluate the effect of the compounds on S. Saintpaul biofilms on stainless steel surface. The MTT assay results showed that the cinnamon EO and cinnamaldehyde at 312 μg/mL and 624 μg/mL respectively could decrease approximately 50% of S. Saintpaul biofilms in polystyrene microplate. The highest reduction of bacterial counts on stainless steel surface was observed with addition of 156 μg/mL and 234 μg/mL of cinnamon EO during biofilm formation. Cinnamon EO and cinnamaldehyde reduced the number of bacterial cells on stainless steel surface, making it a potential compound for Salmonella spp. control.